Analisis Peramalan Penjualan Produk Pada PT.Enseval Putera Megatrading TBK Menggunakan Metode Regresi Linear Sederhana - Abel Arisandi; Usman Ependi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
Procurement of health products becomes effective and efficient so that health products are available with the type and amount according to needs and can be obtained when needed. Forecasting in this study can be used to analyze the predictions of sales of pharmaceutical products so that the level of sales is in accordance with the level of consumer demand so as to assist the planning and control of health products at PT. Enseval Putera Megatrading Tbk. The purpose of this study is to determine the forecasting of pharmaceutical products at PT. Enseval Putera Megatrading Tbk Palembang which can be used as a reference in decision making in planning and controlling the inventory of pharmaceutical products at PT. Enseval Putera Megatrading Tbk